Theories of counseling and psychotherapy - Ivey, Allen E (Allyn & Bacon, 2002)
Previous ed. has title: Counseling and psychotherapy; Includes bibliographical references and indexes; Neal A. Newfield, Ph.D., LICSW (Giver)